2012
DOI: 10.1371/journal.pone.0040857
|View full text |Cite
|
Sign up to set email alerts
|

The Species Identity of the Widely Cultivated Ganoderma, ‘G. lucidum’ (Ling-zhi), in China

Abstract: Ling-zhi, a widely cultivated fungus in China, has a long history in traditional Chinese medicine. Although the name ‘Ganoderma lucidum’, a species originally described from England, has been applied to the fungus, their identities are not the same. This study aims to clarify the identity of this medicinally and economically important fungus. Specimens of Ling-zhi from China (field collections and cultivated basidiomata of the Chinese ‘G. lucidum’), G. lucidum from UK and other related Ganoderma species, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
117
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 28 publications
11
117
0
3
Order By: Relevance
“…Later, it was found that G. lucidum from tropical Asia is not conspecific with G. lucidum sensu stricto, and not even conspecific with the real "Lingzhi" distributed in East Asia, and was named G. multipileum Ding Hou, (Wang et al 2009). Cao et al (2012) Wang et al (2012) proposed that 'G. lucidum' for Chinese species is incorrect and this should be corrected to Ganoderma sichuanense.…”
Section: Introductionmentioning
confidence: 99%
“…Later, it was found that G. lucidum from tropical Asia is not conspecific with G. lucidum sensu stricto, and not even conspecific with the real "Lingzhi" distributed in East Asia, and was named G. multipileum Ding Hou, (Wang et al 2009). Cao et al (2012) Wang et al (2012) proposed that 'G. lucidum' for Chinese species is incorrect and this should be corrected to Ganoderma sichuanense.…”
Section: Introductionmentioning
confidence: 99%
“…However, cultivated Lingzhi varieties were not only incorrectly recorded throughout China, but were similarly reported incorrectly from all around the world. The name of G. lucidum has been applied to collections from North America, East Africa, South America and Southeast Asia, East Asia, Oceania as well as Europe (Wang et al, 2012). The collections named as G. lucidum from different regions of the world have appeared in several separated taxa in phylogenetic biogeographic analyses of the genus Ganoderma (Gilbertson and Ryvarden, 1986;Moncalvo et al, 1995;Gottlieb et al, 2000;Hong and Jung, 2004;Lee et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The use of these techniques is dependent on the ribosomal RNA sequences. Taxonomy of China widely cultivated Ganoderma has been studied by researchers for many decades (Zhao et al, 2003;Luo et al, 2005a, b;Tang et al, 2005a, b;Su et al, 2007;Wu et al, 2009;Zhou et al, 2008;Gao et al, 2010;Huang et al, 2010;Cao et al, 2012;Wang et al, 2012), but numerous taxonomic problems remain and the molecular taxonomy of China widely cultivated Ganoderma has not previously been addressed. Intuitive species boundaries, phylogenetic relationships, distribution and host range of taxa of the G. lucidum complex are really not clear even among the few taxa nowadays recognized in China.…”
Section: Discussionmentioning
confidence: 99%
“…was also identified from Rajshahi, Pabna, Jaipurhat and Dhaka district of the tropical moist deciduous forest region in Bangladesh (Rumainul et.al, 2015) and first found in 1905 by American mycologist named William Murrill (Murrill, 1905). This species was also reported in China (Wang, et al, 2012) and India (Ram, 2012).The species of Ganoderma was reported at the Mangrove forest and tropical moist deciduous forest regions of Bangladesh and India Aminuzzaman, 2017, Copper et al, 2011;Pushpa andPurushothama, 2012).Both of Ganoderma lucidum and Ganoderma appalantum were reported in India and Nigeria (Pushpa and Purushothama, 2012).…”
mentioning
confidence: 84%